2018
DOI: 10.1016/j.celrep.2018.01.073
|View full text |Cite
|
Sign up to set email alerts
|

BK Potassium Channels Suppress Cavα2δ Subunit Function to Reduce Inflammatory and Neuropathic Pain

Abstract: Cavα2δ subunits contribute to the cell-surface expression of Cav2 calcium channels. Upregulation of Cavα2δ-1 in dorsal root ganglion neurons occurs after nerve injury and results in an increased synaptic abundance of Cav2.2 channels in the spinal dorsal horn, thus enhancing the transmission of pain signals. Here, we report that large conductance calcium-activated potassium (BK) channels interact with the Cavα2δ subunit. Coexpression of BK channels with the Cav2 calcium channels reduces their cell-surface expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…Other 2-1 Binding Proteins BK type voltage-gated potassium channels compete with voltage-gated calcium channel 1 subunits for 2-1 protein binding (Zhang et al, 2018). BK channels directly associate with CaV2.1 and CaV2.2 channels at presynaptic endings in brain (Berkefeld et al, 2006;Dai et al, 2009), putting them within a few nanometers of vesicle release machinery at synapses.…”
Section: Jpet # 266056 Page 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Other 2-1 Binding Proteins BK type voltage-gated potassium channels compete with voltage-gated calcium channel 1 subunits for 2-1 protein binding (Zhang et al, 2018). BK channels directly associate with CaV2.1 and CaV2.2 channels at presynaptic endings in brain (Berkefeld et al, 2006;Dai et al, 2009), putting them within a few nanometers of vesicle release machinery at synapses.…”
Section: Jpet # 266056 Page 21mentioning
confidence: 99%
“…This interaction reduces radioligand binding of gabapentin to 2-1 (San Segundo et al, 2019) and gabapentin applied to this complex signals to the presynaptic cytosol to reduces the effective size of the readily releasable pool of vesicles (San Segundo et al, 2019) D. The 2-1 transmembrane domain interacts with an unknown sequence on NMDA receptor NR1/NR2A and NR1/NR2B proteins (red) (Chen et al, 2018) to alter NMDA receptor function. E. BK-type calcium dependent potassium channels (bright green) associate with 2-1 in a mutually exclusive manner with calcium channel 1 (Zhang et al, 2018) but effects of gabapentinoid drugs on BK channels (if any) are not known. F. LRP1 (lipoprotein related protein receptor 1, blue) binds to the 2-1 VWA domain via two extracellular ligand binding domains (Kadurin et al, 2017).…”
Section: Legends For Figuresmentioning
confidence: 99%
“…Gabapentin, which targets the α2δ1 auxiliary subunit of Cav2.2 and dampens α2δ1-dependent VGCC membrane insertion, utilizes an indirect approach and possesses clinical indications for diabetic neuropathy, neuropathic pain, trigeminal neuralgia, and fibromyalgia [7484]. Recently reported competition between the KCa1.1 (BK) potassium channel’s N-terminus and Cav2.2’s pore-forming α subunit for binding to the α2δ subunit further validates α2δ-targeting for analgesic strategies to combat neuropathic and inflammatory pain [85]. However, long-term use of gabapentin is restricted by evidence for its interference with synaptogenesis, and therefore memory formation, through disruption of α2δ1-thrombospondin interactions [86].…”
Section: Dysregulation Of Vgccs In Neuropathic Painmentioning
confidence: 99%
“…Several other recent findings have shed light on novel functions of α2δ-1 in the context of inflammatory and neuropathic pain (see Figure 1). For example, it has been shown that α2δ-1 interacts with the N terminus region of BK potassium channels (Zhang et al, 2018). Co-expression of BK channels with Cav2 channels reduces cell surface expression and whole-cell calcium current density due to competition for α2δ-1 for binding.…”
mentioning
confidence: 99%